Synthesis of Novel 4,5-Dihydro-1,2,4,5-oxatriazine-6-one from the Reaction of Benzonitrile Oxide with 1-Ethoxycarbonyl-1-methylhydrazine - El-Rahman S. Ferwanah, Abed; M. Awadallah, Adel (Asian Journal of Chemistry, 2010)
Benzonitrile oxide (2) reacts with 1-ethoxycarbonyl-1-methylhydrazine3 to give the acyclic hydrazidoxime (4) as a stable product,which cyclizes to the novel 4,5-dihydro-1,2,4,5-oxatriazine-6-one (5) uponstirring with NaH in dry THF at room temperature. The fragmentation of(5) in the mass spectrometer is discussed.